Loss Aversion in Behavioral Finance: Its Effects on Risk-Taking and Market Behavior - Sladkova, Nela (Digital Repository of Theses, 2025)
This thesis explores the loss aversion within the framework of behavioral finance with specific focus on its impact on risk taking and market behaviour. It is able to challenge the assumptions of rational decision making in traditional finance and especially under the Efficient Market Hypothesis (EMH). The use of Prospect theory is used in order to explain the tendency for individuals to feel losses more significantly relative to gains of an equal amount. It analyzes the key behavioural effects such as the Disposition effect and Herding. This thesis utilizes empirical data and secondary sources in order to evaluate the manifestation of loss aversion in the real world and investment decisions. The results of this thesis show that loss aversion leads to suboptimal investment behaviour which includes premature selling of winning assets and holding on to losing ones. In addition the identification of loss averse investors exhibiting greater resistance especially in volatile markets is present. This thesis concludes that behavioural biases significantly affect market efficiency which hence has implications for policy making, due to this it recommends the integration of behavioral insights into financial planning tools as well as regulatory strategies and market forecasting models.